Mechanochromism - Fisher, David (Materials Research Foundations Ser., 2019)
The book Mechanochromism references 325 original resources and includes their direct web link for in-depth reading. Keywords: Mechanochromism, Piezochromism, Piezoelectricity, Triboluminescence, Electroluminescence, Thermoluminescence, Photoluminescence, Stress Recording, Wear Monitoring, Fracture Detection, Pressure Monitoring, Incipient Damage Detection, Shock Wave Effects, Mechanoluminescent Polymers, Nanosensors, Spiropyran, Gold Complexes, Copper Complexes, Platinum Complexes, Iridium Complexes, Tetraphenyls, Diketones, Anthracenes, Acetylenes, Azoles, Thiophenes, Polyurethane, Hydrogels,